The Association Between Influenza Vaccination and Other Preventative Health Behaviors in a Cohort of Pregnant Women. (June 2015) - Scheminske, Megan; Henninger, Michelle; Irving, Stephanie A.; Thompson, Mark; Williams, Jenny; Shifflett, Pat; Ball, Sarah W.; Avalos, Lyndsay Ammon; Naleway, Allison L.; ,
Objectives. Although pregnant women are a high-priority group for seasonal influenza vaccination, vaccination rates in this population remain below target levels. Previous studies have identified sociodemographic predictors of vaccine choice, but relationships between preconception heath behaviors and seasonal influenza vaccination are poorly understood. This prospective cohort study followed pregnant women during the 2010-2011 influenza season to determine if certain health behaviors were associated with vaccination status. Method. Participants were pregnant women receiving prenatal care from Kaiser Permanente Northwest and Kaiser Permanente Northern California. Women were surveyed about preconception smoking, alcohol consumption, and vitamin/supplement use. Vaccination data were obtained from health plan databases and state immunization records. Results. Data from 1, 204 women were included in this analysis. Most participants (1, 204; 66.4%) received a seasonal influenza vaccine during the study period. Women vaccinated prior to pregnancy were more likely to use a supplement containing folic acid (80%) or vitamin D (30%) compared with women who were vaccinated during pregnancy (72% and 15%, respectively) or unvaccinated women (62% and 12%, respectively, p < .001). Women vaccinated prior to or during pregnancy were more likely (75%) to have never smoked compared with women who were not vaccinated (70%, p = .005). There were no significant differences in alcohol use or household cigarette smoke exposure by vaccination group. Conclusions. Women who engaged in specific preconception health behaviors were more likely to receive seasonal influenza vaccination. Failure to participate in these health behaviors could alert health care practitioners to patients' increased risk of remaining unvaccinated during pregnancy.